Jamban Keluarga yang Berwawasan Lingkungan - Faizal Amir; Muhammad Ardi; Bakhrani A. Rauf (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. The objectives of this PKM are as follows: (1) increasing partners knowledge about environmentally safe family latrines, and (2) improving partners skills in making environmentally safe family latrines. When conducting counseling to partners, the methods used are lectures, questions and answers, and discussion. When conducting training and mentoring partners, the methods used are lectures, questions and answers, discussions, and demonstrations. The results achieved are as follows: (1) partners have knowledge about family latrines that are safe for the environment, (2) partners skilled to make the construction of family latrines that are safe for the environment, and (3) partners make one unit of environmentally friendly family latrine and has been used and is functioning properly.